HIV-1 tat promotes integrin-mediated HIV transmission to dendritic cells by binding Env spikes and competes neutralization by anti-HIV antibodies. - Paolo Monini; Aurelio Cafaro; Indresh K Srivastava; Sonia Moretti; Victoria A Sharma; Claudia Andreini; Chiara Chiozzini; Flavia Ferrantelli; Maria R Pavone Cossut; Antonella Tripiciano; Filomena Nappi; Olimpia Longo; et al. (PLoS ONE, 2012)
Use of Env in HIV vaccine development has been disappointing. Here we show that, in the presence of a biologically active Tat subunit vaccine, a trimeric Env protein prevents in monkeys virus spread from the portal of entry to regional lymph nodes. This appears to be due to specific interactions between Tat and Env spikes that form a novel virus entry complex favoring R5 or X4 virus entry and productive infection of dendritic cells (DCs) via an integrin-mediated pathway. These Tat effects do not require Tat-transactivation activity and are blocked by anti-integrin antibodies (Abs). Productive DC infection promoted by Tat is associated with a highly efficient virus transmission to T cells. In the Tat/Env complex the cysteine-rich region of Tat engages the Env V3 loop, whereas the Tat RGD sequence remains free and directs the virus to integrins present on DCs. V2 loop deletion, which unshields the CCR5 binding region of Env, increases Tat/Env complex stability. Of note, binding of Tat to Env abolishes neutralization of Env entry or infection of DCs by anti-HIV sera lacking anti-Tat Abs, which are seldom present in natural infection. This is reversed, and neutralization further enhanced, by HIV sera containing anti-Tat Abs such as those from asymptomatic or Tat-vaccinated patients, or by sera from the Tat/Env vaccinated monkeys. Thus, both anti-Tat and anti-Env Abs are required for efficient HIV neutralization. These data suggest that the Tat/Env interaction increases HIV acquisition and spreading, as a mechanism evolved by the virus to escape anti-Env neutralizing Abs. This may explain the low effectiveness of Env-based vaccines, which are also unlikely to elicit Abs against new Env epitopes exposed by the Tat/Env interaction. As Tat also binds Envs from different clades, new vaccine strategies should exploit the Tat/Env interaction for both preventative and therapeutic interventions.